Self esteem and functional diversity - Almudena Iniesta Martínez; Alicia Martínez Sanz; Carmen Mañas Viejo (INFAD, 2014)
The aim of this paper is to analyse self esteem among people with functional diversity and how it makes a situation of concealment and invisibility conditional on the functional diversity model. To this end life stories of women with physical and sensory functional diversity aged between 16 and 65 years have been selected. The research methodology is of mixed nature. The data analysis was processed by AQUAD 6 (Huber, 2006), arising code series and semantic categories. So through this instructment different narratives of women with functional diversity have been collected. The programme firstly distinguishes between descriptive and demographic and secondly between referential and interpretative codes. Personal evaluations on self-esteem by women with functional diversity are analysed, as well as how they project it onto different aspects of their lives, both personal and social. Results confirm that, in many cases, their personal configuration of self esteem distorts the process of accepting functional diversity.